Multi-Area Automatic Generation Control Scheme including Renewable Energy Sources - Sandeep Bhongade; Barjeev Tyagi; H.O. Gupta (Institute of Advanced Engineering and Science, 2014)
In this paper, a multi-area Automatic Generation Control (AGC) scheme with Renewable Energy Sources (RES) suitable in a restructured interconnected power system has been proposed. Photo-voltaic and wind turbine generating system has been integrated with the grid. The developed scheme has been investigated for frequency control with and without RES units. A PID controller has been used to control the real power output of fossils fuel generators. The parameters of PID controller has been tuned according to Genetic Algorithm (GA) based performance indices. The functioning of proposed scheme has been tested on a 39-bus New England system and on a 75-bus Indian power system network. Frequency regulation market scenario has been considered in both the systems. The results of proposed AGC scheme with and without RES units have been compared.